Styryl silsesquioxane photoresist. Issue 7 (24th September 2014) - Sugita, Hikaru; Tanaka, Kei; Shirato, Kaori; Yamamoto, Ryota; Tateshima, Kazuko
ABSTRACT There is a substantial need for photopattern‐able, heat resistant, and transparent materials that are applicable to electronic devices, such as imaging or display elements. Styryl silsesquioxane based photoresist forms thin micro patterns after i‐line exposure and alkaline development, and the resulting transparent film shows remarkable heat resistance. Radicals generated from a photoinitiator induce polymerization of styryl functionality in the photoresist film to form the micropatterns. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41459.